'Our system fits us': comparing teacher accountability, motivation, and sociocultural context in Finland and Singapore. Issue 4 (2nd October 2022) - Hwa, Yue-Yi
ABSTRACT: Every teacher's classroom practice is embedded in a system of overlapping contexts that interact with their day-to-day decisions. In this paper, I focus on sociocultural context and how it interacts with teachers' subjective responses to accountability instruments. Drawing on interviews with secondary school teachers in Finland and Singapore – education systems with contrasting but comparably effective approaches to teacher accountability – I find that one way in which sociocultural context interacts with teachers' experiences of accountability instruments is by influencing the mental models of motivation that shape their responses to these instruments. This finding is relevant to two contentious areas in education policy. First, it suggests that teacher accountability policy is a socioculturally embedded matter, implying a need for caution rather than recommending specific forms of accountability across the board. Second, it adds to the growing body of evidence demonstrating that 'best practices' from high-performing education systems are contingent on implementation contexts.